Public human resource management : (Longman, 2009)
1 Competing Perspectives on Public Personnel Administration: Civil Service, Patronage, and Privatization / Donald E. Klingner 3 -- 2 What Every Public Personnel Manager Should Know About the Constitution / David H. Rosenbloom, Joshua Chanin 17 -- 3 Human Resource Management in the Federal Government During a Time of Change / James R. Thompson, Robert Seidner 34 -- 4 Personnel and Human Resource Management in the States / Sally Coleman Selden 46 -- 5 Local Government Personnel Administration: Heritage, Contemporary Practice, and Portents / Susan G. Mason, Lana Stein 64 -- 6 Personnel Recruitment and Retention in the Nonprofit Sector / Beth Gazley 79 -- Section 2 Techniques 93 -- 7 Strategic Human Resources Management / Joan E. Pynes 95 -- 8 The Trials and Tribulations of Performance Appraisal: Problems and Prospects in the Twenty-First Century / Dennis M. Daley 107 -- 9 Employee Benefits / Gary E. Roberts 123 -- 10 Challenges in Motivating the Public Sector Employee: Theory and Practice in a Dynamic Environment / Gerald T. Gabris, Trenton J. Davis 142 -- 11 Human Resource Metrics in Government: Measuring the Impacts of HRM / Steven W. Hays, Robert Lavigna 160 -- 12 Planning for Today and Tomorrow: Workforce Planning / Willow S. Jacobson 179 -- 13 Employee Rights to Address Wrongs: Trends in State Government Grievance Practices / Jessica E. Sowa 203 -- Section 3 The Issues 217 -- 14 Affirmative Action and Diversity in the Public Sector / J. Edward Kellough 219 -- 15 Gender and Workplace Issues / Mary E. Guy, Susan Spice 236 -- 16 HR Information Technology Systems in State Government: Findings from the 2007 Government Performance Project / Robert T. Wooters 253 -- 17 Ethics and Human Resource Management / Jonathan P. West 275 -- 18 Current Developments in Public Sector Labor Relations / Patrice M. Mareschal 290 -- 19 Outsourcing Human Resources: Problems and Prospects for the Public Sector / Jerrell D. Coggburn 308 -- 20 Turbulence in the Civil Service: Whither the Public Service Ethos? / James S. Bowman 327.